Upper intestine - New target for type-2 diabetes: A review - Martha, Srinivas; de las Heras, Javier; Ramreddy, Srividya; Veldandi, Uday K; Pantam, Narayana (Asian Journal of Medical Sciences, 2011)
Type-2 diabetes is a chronic metabolic progressive disease, affects 200 million people worldwide will leads to increased death by more than 50% in the next 10 years. The ingested nutrients stimulate the release of gut peptides called incretins, which enhance the insulin secretion from pancreatic β cell, in addition to this, recently, another gut mediated mechanisms called intestine-brain-liver axis to regulate glucose homeostasis by a neural circuit, initiated in the intestine in response to nutrient sensing, that increases sensitivity to insulin levels. In this mini review, the underlying mechanisms of gut related glucose regulation and its impact on the management of type-2 diabetes mellitus. Key Words: Type-2 diabetes; Intestinal nutrients; Long chain fatty acids; intestine-brain-liver axis; metabolic surgery DOI: 10.3126/ajms.v2i1.3403 Asian Journal of Medical Sciences 2 (2011) 56-62